Upaya Meningkatkan Budaya Literasi di Sekola Dasar Melalui Implementasi Progam Kampus Mengajar - Ahyar, Ahmad Miftahul; Zumrotun, Erna (Institut Agama Islam Daruttaqwa Gresik, 2023)
The Merdeka Learning Campus Merdeka Program (MBKM) was launched by the government, under the Ministry of Education, Culture, Research, and Technology (Kemendikbutristek), initiated a program aimed at assisting Elementary Schools impacted by the pandemic. This initiative has been designed to address the challenges faced by each UPTD Elementary School. The primary focus of this service is to assess the effectiveness of the Teaching Campus program in enhancing literacy culture at SDN 1 Bringin. The study adopts descriptive qualitative research techniques to methodically present the observed facts. Data collection involves conducting interviews, documenting information, and directly observing the situation. The process of increasing literacy culture is carried out through the School Literacy Movement (GLS) with a release program, namely: (1) reading circle, (2) living library and (3) reading Tuesday. The results of the study revealed that the